Quand l’enseignant « bricole » : une adaptation entre inconscience et rationalité - Dominique Alvarez; Sandra Cadiou; Patricia Mothes (Éducation et Socialisation)
In their daily work, teachers have to deal with a multitude of unforeseen events and constantly adapt. We observe the unconscious dimension of « bricolage ». Our work is based on three clinical didactic vignettes. These three cases show the unconscious dimension of their adaptation, which is driven by their already there and the various reasons for this adaptation. Between the impossible to bear, the subject supposed to know and the maintenance of the psychic space of the classroom, various concepts stemming from a psychoanalytical orientation allow us to better grasp the processes of unconscious « bricolage », and give us orientations for the training of teachers.